Giant Hydatid Cyst of the Interventricular Septum. Issue 3 (26th October 2015) - Parakh, Neeraj; Jagia, Priya; Hote, Milind; Arava, Sudhir
Mini‐Abstract: This case illustrates one of the largest reported hydatid cyst of the interventricular septum that almost obliterated both ventricular cavities. Diagnosis of hydatid cyst was confirmed on echocardiography, cardiac MRI, CT chest, and postoperative histopathology.